Proceedings of the conference on the rehabilitation and reconstruction of buildings CRRB 2012 : selected, peer reviewed papers from the Conference on the Rehabilitation and Reconstruction of Buildings 2012 (CRRB 2012), November 6-7, 2012, Brno, Czech Republic - Conference on the Rehabilitation and Reconstruction of Buildings (14th : 2012 : Brno, Czech Republic); Drochytka, Rostislav; Vanerek, Jan, editor (Durnten-Zurich : Trans Tech Publications, 2013)
Includes bibliographical references and indexes